Beneficial effects of nerolidol on thioacetamide-induced damage of the reproductive system in male rats - Celik, Huseyin; Camtosun, Ahmet; Ciftci, Osman; Cetin, Asli; Aydin, Muhterem; Gurbuz, Sukru (Allied Acad, 2016)
In this study, it was aimed to determinate beneficial effects of Nerolidol (NLR) against reproductive toxicity caused by Thioacetamide (TAA). Male, 3-4-months-old, rats (n=32) were divided into four groups. Group-1 was kept as control and given corn oil as carrier. Group-2 received TAA (200 mg/kg, intraperitoneal (i.p.), two times per week) for 3 weeks, in group-3; NRL was orally administered at the dose of 100 mg/kg per every other day by gavages, group-4; 200 mg/kg TAA and 100 mg/kg NRL were given. Thiobarbituric Acid Reactive Substances (TBARS) and reduced Glutathione (GSH) levels, Catalase (CAT), Superoxide Dismutase (SOD) and Glutathione Peroxidase (GPX), sperm parameters and reproductive organs weight were determined. TAA caused a significant rise in TBARS level and a significant reduce in GPX, CAT, SOD and GSH levels in the testicular tissues compared with the control group, while NLR led to significant reduce in lipid peroxidation via decreasing TBARS level and increasing the levels of GPX, CAT, SOD and GSH. Besides, sperm parameters significantly reduced, and pathologic testicular damage increased with TAA exposure. However, these effects of TAA on sperm parameters and histopathological changes were reversed by NLR treatment. In conclusion, our results demonstrate that the management of TAA induced the testicular damage and NLR prevented thioacetamide-induced testicular damage in rats.
Keywords: Nerolidol; Thioacetamide; Rat; Experimental; Testicular damage